AN AUDIT OF CAESAREAN SECTION IN DISTRICT HEADQUARTER TEACHING HOSPITAL, GOMAL MEDICAL COLLEGE D. I. KHAN - Irum Batool Hashmi1 , Neelam Mehsud2 , aimen saleem 3 , Muhammad Hamayun 4 , Fauzia Afridi5 , Sarmad Saeed Aziz6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
Abstract Background: There is a global concern for rise in CS rate over the past few years. C-Section (CS) deliveries are not only associated with high morbidity and mortality but also prolonged hospital stay and a general financial burden. Objective: To analyze the rate and frequency of different indications of CS in DHQ teaching hospital D. I. Khan-KPK, Pakistan. Place and duration: This cross sectional study was conducted at the Gyne and Obs department of DHQ hospital D.I.K. from January 2015 to December 2020. Patients and Methods: A total of 25884 delivery cases were entertained during the study period. Detailed gynecological and obstetrical history was recorded using a pre designed questionnaire format with an informed consent. All the base line investigations were carried out. Strict fetometernal monitoring was done during labour period. Prostein E2 tablets were used for induction using Bishof score. Clinical record of all patients including mode of delivery and indications were analyzed in terms of percentage and frequencies. Results: Out of 25884 patients enrolled in the study, 11.6% (n=3009) were delivered by CS 88.4% (n=22875) delivered by vaginal birth. Rate of CS ranges from 8.9% to 12.5% between January, 2015 to December, 2020. Whereas the mean rate calculated was 11.6%. Audit of different indications of CS for January 2015 to December 2020. Audit was divided into two broad categories for an emergency and an elective CS. The most common indication for an emergency CS was primary breech (10.80%) followed by fetal distress (7.80%), obstructed labour (7.40%), cephalo pelvic disproportion (5.54%), and previous-I (6.60%). The most common indications for an elective CS were previous-I (6.05%), previous-II (4.20%), cephalo pelvic disproportion (4.03%), breech (2.50%) and previous-III (2.1%). Conclusion: We concluded from our findings that rate of CS was low at our unit but still it needs to be closely monitored and audited so as to take measures to keep the check on CS rates. Assisted vaginal breech delivery should be encouraged to reduce CS rate for this indication.